2019
DOI: 10.3390/v11111019
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Natural Products as Effective and Broad-Spectrum Anti-Zika Virus Inhibitors

Abstract: Zika virus (ZIKV) infection during pregnancy leads to severe congenital Zika syndrome, which includes microcephaly and other neurological malformations. No therapeutic agents have, so far, been approved for the treatment of ZIKV infection in humans; as such, there is a need for a continuous effort to develop effective and safe antiviral drugs to treat ZIKV-caused diseases. After screening a natural product library, we have herein identified four natural products with anti-ZIKV activity in Vero E6 cells, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 58 publications
5
66
1
Order By: Relevance
“…In their initial screen in Vero E6 cells, curcumin (amongst other compounds) had a lower IC 50 (~5-14 µM) relative to CC 50 (~53 µM) against several strains of ZIKV as determined by plaque assay. Time-of-addition assays again suggested that curcumin exerts anti-ZIKV activity through an ability to interfere with cell attachment [15]. Taken together, these studies demonstrate curcumin's potential against ZIKV.…”
Section: Zika Virusmentioning
confidence: 72%
See 4 more Smart Citations
“…In their initial screen in Vero E6 cells, curcumin (amongst other compounds) had a lower IC 50 (~5-14 µM) relative to CC 50 (~53 µM) against several strains of ZIKV as determined by plaque assay. Time-of-addition assays again suggested that curcumin exerts anti-ZIKV activity through an ability to interfere with cell attachment [15]. Taken together, these studies demonstrate curcumin's potential against ZIKV.…”
Section: Zika Virusmentioning
confidence: 72%
“…Protein expression Enterovirus 71 [13] Conformation of viral/cellular surface proteins Viral attachment Zika virus Chikungunya virus Vesicular stomatitis virus [14][15][16] Human respiratory syncytial virus [17,18]…”
Section: Cleavage Of Eif4gmentioning
confidence: 99%
See 3 more Smart Citations